Osmanlı para sisteminin teorik temelleri - Bal, Oğuz (My University, 1998)
İslami Ekonomik Düzen, Kuran'da bulunan bir dizi ilkeye dayanıyor. İçinde İslam ekonomisi, mücadelenin yerini işbirliği yaparak değiştirdi. İşbirliği sadece bir hareket. Aynı zamanda bir motif ve psikoloji. Aynı zamanda bir neden ve bir rehberlik prensibi olan bir mantık ve ruh hali insan girişiminin tüm alanlarına yayılıyor. İslam bir din değildir. Sınırlı bir anlamda kelime ancak insan hayatının her yönünü kapsar ve ister. Geliştirmek istiyor insanda yeni bir ahlaki kişilik, entegre bir toplumsal varoluş ve yeni bir sosyo-ekonomi ve siyasi düzen. Ekonomik-kavramlar, hedefler, yöntemler, yasalar ve araçlar. İslami ekonomik sistem doğrudan ya da kapitalizm ya da sosyalizm ya da komünizmin herhangi bir türü. Temel fark şu: İslami ekonomi ilahi rehberliğe dayanıyor; buna karşın kapitalist ve sosyalist ekonomi dine atıfta bulunmadan belirli bir insani eylem önermektedir. İslamcı Ekonomi kavramı mülkiyeti yöneten temel ilkelerden kaynaklanmaktadır. Var Allah'ın servet ve mülk hakkında koyduğu açık ve kesin yasalar. Endişe ediyorlar edinme, kullanma ve elden çıkarma ve mülkiyetin her biçimi ile ilgili olması özel kullanım, ticaret, tarım, endüstri veya başka herhangi bir amaç için. Hükümet kurallarını Propety'nin edinimi, Helal ifadesinde özetlenmiştir. İslam korur ve korur tüm koşulların hâkimiyeti. İslam, rekabete izin verir, ancak mükemmellik konularında. Sosyal ticarette Rehberlik ilkesi bu işbirliğidir. Bir ortak taahhüt altındaki adamların birleşmesi enterpnse; İstenilen sonuca ulaşmak için farklı beceri, yetenek ve varlıkların kombinasyonu ile mutabık kalınan oranlarda tam sorumluluk, güven ve fayda payı; ve basit bir başkasının ihtiyaçlarına hitap ederek yaşamak isteyen hareket,Ekonomik işbirliği. Bu ekonomik işbirliği, eşitlik doktrinlerine ve adil muamele. İslamiyet öncesi Arapların parasal sistemi yoktu ve paraları yoktu. Prensip olarak Aralarında Fars ve Bizans paraları yasal ihalelerdi. Ve bu madeni paralar nadir ve eşit olmayan ağırlıklar, İslam öncesi Arabistan'da para, bazen de olsa taşır Parasal ödeme ile, gerçekte bir banker anlaşmasıydı. İslam'ın erken dönem ticareti tamamen ekonomik bir hareket olarak değil, aslında bir ahlâki eylemi olarak görülüyordu. Bankacılık yeni olmadığı gerçeği göz ardı edilmemeli; erken dönemlerde bile varoldu Hazreti Ömer, Beyt'l Mal'ı kurdu ve bu da Kard'l Hasna'yı sadece kişisel tüketim için değil aynı zamanda iş için de muhtaçtır. Kâr hem taraflarca paylaşıldı banka ve tüccar. Daha sonra, Abbasiler döneminde bir dizi banka kuruldu hangi lahbaza denir. Bu bankalar sadece mevduat kabul etmekle kalmıyor aynı zamanda işadamları ve verilen ve kabul edilen çekler, taslaklar. Bu nedenle, İslami finansal sistem, Riba, ancak yalnızca İslami sosyal adalet ilkelerini benimseyerek ve kanunları getirerek, uygulamalar, usuller ve adalet, hakkaniyet ve faimess. Bankacılık operasyonlarının nah.rre'u herhangi bir finansal sistemin işleyişinde merkezi. Birçok İslami finans kuruluşu şimdi Müslüman dünyanın çeşitli paru işler durumda. Bu kurumların hedefleri Müslümanlar tarafından istenen tüm finansal operasyonların taahhüdünü, İslam hukukunun ilkeleri ve kuralları; bu fonlardaki yatırımları kapsar İslam bağlamı, Helal kâr nesiller ve konsolidasyon, tanıtım veİslami mali operasyonların uluslararası işbirliği. Günümüzde işlev gören çeşitli İslami finans kuruluşları, bankacılık, finansman ve yatırım perasyonlarının rekabetçi bir temele dayandırılması. -Bankacılık sistem cari hesaplar, hesaplar tasarruf, sistematik tasarruf hesapları, sabit yatırım hesapları ve çağrı yatırım hesapları. Finansman çeşitli alanlarda yapılmaktadır. yolları. Kısa vadede ticaret, kabul * d hir. satın alma. üzerinde ben orta vadede kredi, canlanma gelişme kredileri ve kira finansmanı konularını kapsar. üzerinde Uzun vadeli olarak, mortgage,

sermaye finansmanı ve proje finansmanına kadar uzanır. bir uluslararası bankacılık işlemleri, para ve emtia alım satımı, para transferi, ihracat finansmanı, akreditifler ve teminat mektupları. Geleneksel bankacılık sisteminde kişisel veya kurumsal krediler yapılır basit bir finansman mekanizması aracılığıyla. Finansal aracı olarak hareket eden bankalar, kamuoyundan depozitler çıkartıp ödünç verenlere ödünç verirler. Borçlular, bireylerdir veya kurumlardır. Bankaların kârı esas olarak depozitlerle harcanan (ödenen) faiz ile kazanılan faiz (alınan) arasındaki fark borçlulardan. İslami bankacılık sisteminde The Islamic Economic Order is based upon a set of principles found in the Quran. In lslamic economy, struggle wrll be replaced by co-operation. Co-operation is more than just an act. It is also a motive and a psycology. It is at once a cause and a guiding principle , a reason and a mood pervading all spheres ofhuman enterprise. Islam is not a religion in the limited sense of the word but covers all aspects of human life and wants. It seeks to develop a new moral personality in man, an integrated social existence and a new socio- economics and political order. It has its own approach to economic-concepts, objectives, methods, laws and instruments. The Islamic economic system is not directly related to either capitalism or any variants of socialism or communism. The fundamental difference is that the Islamic economy rests upon Divine guidance whereas capitalistic and socialist economics propose particular human action without reference to religion. The Islamic concept of economics originates from the basic principles governing property. There are clear and precise laws laid down by Allah about wealth and property. They concern the acquisition, use and disposal of property and relate to all forms of property whether it is for private use, trade, agriculture, industry or for any other purpose. The rules goveming the acqusition ofpropety are summarised in the expression Halal. Islam protects and safeguards the dignity ofrndivrdual rn all circumstances. Islam allows competition but only in matters of excellence. In social commerce, the guiding principle is that co-operation. Assocation of men in undertaking a common enterpnse; combination of different skills, talents and assets in pursuit ofa desired end, with full responsibility, trust and share in benefit in muhrally agreed proportions; and the simple act of seeking out one's living through catering to another man's needs, are all acts of economic co-operation. This economic co-operation is further by the doctrines of equity and fair dealing. Pre-Islamic Arabs had no monetary system and no coins of their own. Principally Persian and Byzantian coins were legal tenders among them. And since these coins were rare and were of unequal weights, money in Pre-Islamic Arabia, though sometimes carried on by monetary payment, in reality, it was a banker deal. Trade in the early Islamic period was not considered purely economic act, but indeed as an act of morality. The fact should not be ignored that banking is not new; it existed even in the early days of Islam, Hazrat Omar established Beyt'l Mal which advanced Qard'l Hasna to the needy not only for personal consumption but also business. The profit was shared both by the bank and the trader. Later on, during the Abbasid period a number of banks established which called lahbaza . These banks not only receives deposits but also advanced loans to businessmen and issued and accepted cheques, drafts, respectively. The Islamic financial system, therefore cannot be introduced merely by eliminating Riba, but only by adopting the Islamic principles of social justice and introducing laws, practices, procedures and justice,equity and faimess. The nah.rre of banking operaiions is central to the functioning of any financial system. Many Islamic financial institutions are now functioning in various paru of the Muslim world. The objectives of these institutions include the undertakrng of all financial operations required by Muslims in the framework of principles and precepts of Islamic Law; this embraces the investment of funds v/ ithin the islamic context, the generations of Halal profit and the consolidation, promotion and cooperation of Islamic financial operations intemationally. The various Islamic financial institutions fonctioning today are carryrng out a variety of banking, financing and investment operations on a competitive basis. -The banking system handles current accounts, saving accounts, systematic saving accounts, fixed investment accounts and call investment accounts. Financing is being d6ne in a variety of ways. on a short -term basis, it is carried out for trade, acceptance *d hir. purchase. on I a medium-term basis, it covers loans, bosiness development credits and lease financtng. On a long term basis, it is extended to mortages, equity financing and project financing . An international banking transactions, purchase and sale of currencies and commodities, taransfer of funds, export financing, letters of credit and letters of guarantee. In the conventional banking system, personal or corporate loans are performed through a simple financing mechanism. The banks, acting as financial intermedianes, accept depozits from the public and lend them to the borrowers, regardless of whether these borrowers are individuals or corporat€ entities. The banks profit are mainly attributed to the difference between interest expended (paid)to depozitors, and interest earned (received) from borrowers. In the Islamic banking system the issue is rather more complicated. Money does not earn money without a collaboration between capital and effort. Therefore depozitors do not eam an automatic fixed return on their depozits as in the conventional system. Islamic instruments take one or more of the following forms: Mudaraba Musharaka, Murabaha and Ijara wa Iktina. The definitions and mechanism surrounding each type are discussed in this study. Mudaraba (capital trust) was a pre-Islamic custom used to finance a significant portion of the caravan trade of Arabia. Oriantalists beleive that'commenda', as it came to be known in the Medieval West around the tenth century, was adopted from the Islamic commercial practice that was in operation as early as the sixth century. The best known and, probably the most widespread, classical Islamic partnership was the mudaraba. The mudaraba was an arrangement in which an investor entnrsted his capital or merchandise to an agent (mudanb) who trades with it and then returns to the investor the principal and a previously agreed -upon share of profits. As a reward for his enterpreneurship, the mudaribreceives the remaining share ofthe profits. Any loss resulting from the exigencies of travel or from an unsuccesful business venture was compensated exclusively by the investor. The mudarib was in no way liable for a loss of this nahrre, to sign only his expended time and efforts. In this snrdy we have tried to establish that mudaraba (simple profit -sharing) is a way of corporation among different factors of productions firmly rooted in the eur'an and Sunnah . it has been in practice throughout Islamic history. We have seen that profitsharing can be applied in all sectors of economy: trade, industry, services and agriculture. In terms of fairness, sharing ranks higher than hiring. We have also noted that when interest is abolished, it is a must to allow profit-sharing in its vanous forms in all sectors of economy. we have concluded that profit-sharing is especially suited to financial sector and that a financial system based on profit -shanng is superior to one based on interest. In jurisprudence terms, Mudaraba is a contract in profit sharing, with one party providing funds and the other the work. In other words, Mudaraba (or eirad) is a contract between two parties: an Islamic bank as an investor (Rab al-Mal) that provides a second party, the entrepreneur (Mudareb)with financial resource to finance a particular project. Mudaraba is best adopted in project and trade financing. The contrachral relaiionihip between the Islamic bank and depositors or between the bank and entrepreneur varies with respect to source of funds utilised. The application of Mudaraba in financing current Islamic banking operations is very limited owing to the restrictions. Trying to assing labels to new financial instnrments serves only to confuse the issue and may not be ap,licable given the new realities ofbusiness finance and its complexities. Musharaka financing is a well established partnership cotract in Islamic Law and was operativ€ in the early Islamic period. it is also one of the most popular means of financing, outside banking system, among commercial or small industrial secton in Arabic and Islamic cities. It is in the area of profit-sharing and the other classical Islamic partnership form. In II musharaka, the musharik(entrepreneur)seeks a greater profit share than it is possible in mudarababecause he takes greater risk in musharaka.. Partnership and is capital input, in addition to his entrepreneurial input which qualifies musharaka bears the same characteristics as that ofthe mudaraba. In the context of Islamic banking, Musharaka is described as a joint venture between an Islamic bank and a costumer or business entity geared for certain operations and may terminate within a specified period of time, or when certain conditions are met. Contrary to Mudaraba, the two partners in Musharaka padcipate in the capital of the venture. If losses occur, they are borne by the partners in proportion to their contribution to the capital. The Islamic bank may finance industry, trade and real estate and contract with almost all legal enterprises through equity or direct participation. Musharaka is well suited for financing private or public companies and particularly in project financing for shortmedium- and long term penods. In the Islamic system, borrowing at a fixed interest rate from a commercial bank is forbidden. Clearly circumstances may arise when Musharaka financing may be set alongside with fixed interest borrowing; should this happen, the Islamic bank may be prepared to take steps to renew the interest borrowing. Murabaha(mark-up sale) is available for financing the purchase or import of capital goods, consumption goods or raw materials. Under the agreement, the customer informs the bank with the specifications and quotations of the goods to be purchased. The Islamic bank studies on the documents with reference to the price,specification and conditions for payment . In many instances the bank may be able to obtain the same goods from a different supplier at more favourable conditions than those obtained by customer. When the bank and its customer have agreed on the terms ofthe deal, the former purchases the goods or commodities and passes the title to the customer at a later date. The profit occuring to the bank is mutually agreed as mark-up on the cost of purchase. There are certain fundamental principles attached to Mudaraba which are overlooked in the existing literature. Ijara(lease financing); the exact meaning ofthe term Ijara is reward or recompence. Its use had started before Islam and was regularised during the early expansion of Islam and has now been adapted to modem needs. Ijara financing is based upon valuing the financial position ofthe client and the expected direct cash flow ofthe lease contract wrthout taking the interest into consideration Generally the Islamic banks are currently involved in spot cash markets. Future contracts are permissible within boundaries: ( l)Future (BayaJi Ajal) sales require the transfer of the goods to the possesion of the buyer while payment will be due in the future and would be higher than in cash sales. (2)A1-Salam(forward buying) requires cash payment in considerations for goods, that will be delivered in the future. Salam contract stipulates the specific identification and determinafion of the commodities in terms of weight, measurement index, and duration of the contract. Bay' mu'ajjal and bay' salam are permiued in Islam. In this contract of sale, price of a commodity is allowed to be different from spot price, if time element is involved in the process of exchange. This can be considered as sort of a recognition of time value of money. Rents and wages also include a fixed reward for the time element. Rent of a house, for example, includes a part which is beyond depreciation . This part of rent can be regarded as time value of money. Thus, while Bay' mu,aiial, rent and wages include a fixJd and predetermined element as compensation for time, prohibition of interest specifically denies any recognition for time value money. The commissioning of a craftman to perform a given task is the prototype of all sale conracts based on immediate payment for an object Io be provided in the future; such conracts, known x salam, are recognired by custom. There is connection between the hadith prohibiting the sale ofyet nonexistent goods and the salam III contract. In parallel rvith islisru' and salam, immediate delivery of goods or services is against payment. The following types of sale are also allowed. (3) Tawliya(break-even sale), to sell at cost ( ) Wadi'a; to sell at a discount. These articles mentioned above are in order to finance projects, trade, industry and agriculture etc. A set ofbasic types of Islamic contracts are based upon Murabaha(cost plus financing), Musharaka(trust financing), Ijara(Lease), Ijara wa Iktina (lease purchase) and Qard Hassan (interest-free loans). It has been proved through expenence that these Islamic forms of contracts can be adapted to new economic situations. The Islamic banking system depends upon participation in profit and loss. The Islamic banks can be developed only if such payments of profit participations are granted fiscal equality with the payments of interest. Thus, changes in legislation need to take place where necessary, to ensure that profit participations and similar payments made by a person or corporation to an Islamic bank are deductible in computing the taxable income of the payer under local law as a busrness expense. This study named Theoretical Fundamentals of Ottoman Monetary System consisted of six sections. Fundamentals of Ottoman Monetary System had been based on Islamic Economics. This foundation is explained one by one under main sections ofBay', Qard, Salam. The study has been begun with legal spesific frame that includes the concept of'contract . In the first section legal frame is determined. The concept of contract is examined. It is explained that the exchange is a contract. The fiqh principles of Ottoman Monetary System is determined examining its conditions, element, classes and formations one by one. In the second section, some means of exchange such as money and quru;y money are explained. The principles rest on monetary system are stated. Monetary systems, its kinds and standards are examined using modern analysis and Ottoman Monetary System based on Islamic Monetary System . In addition, views of scholars about functions of money, its value, inflation and deflation are explained . The subject is discussed by using different fiqh books. Views of independent scholars are compared among themselves in the footnotes. In the third section, foreign exchange system was explained. The tem foreign exchange is explained together with its both nzurow and large means. Foreign exchange, its rate, arbitrage, determination ofthe rate, its system and their effectg policies, devaluation and its conclusions, exchange rate control, its markets and evalution of international monetary institutions were explained under the frame of contemporary economic theories. After these, foreign exchange in Islamic Economy on which Ottoman economy is based was explained in historical process. This process had continued from early Islamic hstory to the middle of the nineteenth century. The principles offiqh had been current in those times every where in Ottoman countries. The term foreign exchange,' is synonym of sarf'. Under the Islamic foreign exchange system, methods of finance , principles of profitJoss partnership and credit finance are summarized one by one. The term sarf in Islamic Economy and the terms related with it are explained. It is processed that transaction of sarf, its conditions, methods of selling, its legality, kinds of sarf, transactions between foreign exchanges, etc.. are under the frame of muslim scholars. Different views are demonstrated like in the footnotes offirst and second sections. one of the fundamentals of ftoman Monetary System is examined under the title of credit in the fourth section. This subject had been examined under the title of ..eard,,in the fiqh books. The systematic of credit system is explained as in the pre,rious sections. Philosophy of credit in the Islamic thought is summurized after its definition, kinds and markets are stated. The subjects are examined as wakala, Hawale and insurance explaining principles of Islamic Economy. The term of Qard in the Islamic Ekonomy is discussed both by means of dictionary and of tecnical term and relations between the means are determined. For readers, subject's legality was acquainted and proved by its documentary. The views of scholars about formation of contract and place, time and methods of payment, are explained comperatively. The subject was finished with judgements about contract of qard. All ofthe fiqh books and views were shown in the footnotes. The Salam was examined in the fifth section explaining the utility both for macro and micro economics . Salam is one of the kinds of credit and it is applicated from Prophet's time to today. If the necessary precautions were taken, documents organized by sides fulfill the functions of money. In this way, money supply, one of the causes of inflation, perhaps could be controlled. Thus, salam can perform the activity money in the markets and investors can provide finansical resources. As stated above sections, both dictionary and tecnical means of salam are explained. Relations between these two means were mentioned. In addition, the terms connected with salam such as Salaf', Dayn, Ayn, Misli, Kryam|, Zrmmat were explained. Nine conditions of salam were counted and tkee practices about it were stated explaining the nature of salam and its legality. All the nine coditions should exist in the contract of salam; if not it might be uncurrent. Approaches of Islamic scholars relating to appropriateness of the analogy was explained. That salam is a contract and its elements were explained one by one. The characteristics of salam, time and ways of payment were explained in the frame of scholars' views. The conditions of payment with ready money and matunty was dwelled upon. The spoiling of salam contract is expalined in an apart subject. Views of scholars were stated in daail for this subject. Finance of order was examined under the title rstrsna'. Istrsna'is a term belongs to fiqh of Islam. The content of this term that is current at contemporary economics was explained. The subject was analyzed . Its conditions and how is it realized was explained systematically. The subject banking was examined in the sixth section. Firstly historical prosses of banking system was explained. It was a tradition coming from early Islamic time to today. The companies mufawada, '1nam, commenda, and their functions are defined. In addation the five typies in the early times are explained. They are mudaraba or muqarada,,, Inan, Abdan, wujuh The subject of credit and money are recounted too. The views of sholars coporosionally are written. The structure of notion actions ofbanking under the principles Islam are determined. These foundations are basing to the Wadia' and Hawala. The relations between the Islamic religion and karlets was explained. The means and aims of markets money and capital was explained one by one. The relations with system of excahange what being and functions under the Islamic economy wils statemented. The actions of interest bearing and interest free was comparatived. Finally, it was proved that the actions of interest-free to actions of interestly can being alternative. Islam is command to avoid from transactions interesly. For that reason people should resourch profit ways other then interest - In regard to compound interest charged by indigenous bankers and money lenders for consumption purposes, the consensus of opinion was that it amounted to Riba and was, therefore strictly forbidden. There is a healthy debate amongst Muslim scholars about the application of sharia law in the financial fields. Although the law itself is clear. its translation into modem, rapidly evolving financial practice is inevitable and open to different interpretations. Islamic tranks have attempted to build up a common code of practice. Although the principles of Islamic finance are well known and there is a substantial literature and the methods of financing involved, the documentation on actual practice is meagre and usually unpublished. There has been a number of studies in recent years on the working of particular Islamic financial instutions, but most of them concentrate on the broad development of the banks concemed, and examine their deposit and lending policies in general terms. There is no practical guide to Islamic financial instruments, and no universally acknowledged standard reference manual for Islamic bankers fellow. Indeed, there appears to be considerable divergence in Islamic financial practic€ between institutions in the same line of business. No Islamic institutions can guarantee a depositor's retum, for example, it does not guarantee the value of deposits which can be adjusted according to the institution's financial performance. There are, however, some instituhons which provide a guarantee. Is this an Islamic practice? Western banks seeking to offer Islamic banking services are confused by the prevailing variations in practrce. Ther is no international Islamic accounting standard, and most Islamic banks are subject to conventional audits, as well as speciafically religious audits. The coventional audits are sometimes carried out by western firms of accountants.
Keywords: Economic history; Ekonomi tarihi; History; Money; Osmanlı İmparatorluğu, 1299-1918; Ottoman Empire, 1299-1918; Para; Tarih; Turkey; Türkiye